Pendeteksi Sinyal Jual/Beli Saham dengan Fuzzy Rule-Based Evidential Reasoning dan C-means Clustering - M. Lutfi Sulthon A.S.; Agung B. Prasetijo; Maman Somantri (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2018)
Stocks are securities indicating the share of ownership of a company. In stock market, most of traded stocks fluctuate in price at all times and traders take an advantage for taking profit. Traders often use technical analysis to determine the trend of stock price movements. The problem is on how traders take positions (buying/selling stocks) with minimal trading decision so they can maximize profits. Fuzzy rule-based evidential reasoning approach can map the conditions of stock movements. Clustering can help the mapping conducted with a high degree of equality with each other. One of the clustering methods is fuzzy C-means clustering. This method is used to determine the number of membership functions for each attribute. To increase profit/Return of Investment (ROI), verification of output decision is required to analyze stock trends when placing buy or sell. From the results experimented, an ROI of 83.80% profit is obtained.